Optimasi Jenis dan Konsentrasi Plasticizer terhadap Kualitas Fisik Sabun Kertas: Pendekatan Desain Faktorial - Lu'lu' Fadlila 'Aziz; Haryanto (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2026)
Paper soap is an innovation of solid soap in the form of thin sheets that is practical for travelling, but excessive brittleness remains a production chalenge. This study compare the effect of five types of plasticizers (glycerin, propylene glycol, polyethylene glycol (PEG-400), sorbitol, and sucrose) at five concentration levels (0%, 5%, 10%, 15%, and 20%) on the physical quality of paper soap based on SNI 2048:202 standars. The experimental study used a 5x5 factorial design with MANOVA analysis to test flexibility, pH, foam stability, and dissolution time. Glycerin 20% showed optimal results: high flexibility (14,67-fold), foam stability of 91,56%, dissolution time of 105 seconds, and pH 9,06. Sorbitol 15-20% can be an alternative with a higher pH, but moderate flexibility. PEG-400 and sucroese showed low flexibility despite accelerating dissolution. Glycerin 20% is the optimal formulation as it provides the best balance between flexibility, foam stability, and dissolution. The selection of plasticizer and their concentration must be done simultaneously to obtain optimal paper soap quality.